Upgrading The Quality of Indonesian Youth: A Case Study at Taruna Nusantara Vocational High School, Magelang, Indonesia - Mustaqim Mustaqim (Nadwa: Jurnal Pendidikan Islam, 2022)
This study aims to prove that highly disciplined learning practices can improve youths' knowledge, attitudes, and behavior in accordance with their national values. This study utilized a qualitative, descriptive-analytical methodology with interviews, observation, questionnaire-complementary techniques, and documentation by Milles and Huberman’s analysis. The findings show that the high-discipline learning strategies in Taruna Nusantara Vocational High School include; first, the addition of archipelago subjects and state defense education; second,  pilgrimage activities to the hero’s graveyard; third, the tracing back of great General Sudirman’s life; fourth, the creation of a song entitled “Bela Negara” which must be memorized and sung by all students; fifth,  study tours to the Military Academy (AKMIL), Air Force Academy (AAU), Police Academy (AKPOL), attorney, court, special forces command (KOPASSUS), Diponegoro Museum, Indonesian national army (TNI) Headquarters, Indonesian Police Headquarters, and the Presidential Palace; sixth, saluting the Indonesian flag every time entering and leaving the classroom can strengthen and improve the quantity and quality of knowledge, attitudes, and behavior of youths following national values. This is evident from the fact that the students have followed the student life norms, which contain national values, up to 90%. 3% of students had a high national attitude, 42.3% had a very high attitude, and 42.7% had an extremely high attitude, totaling 88%. It means that high-discipline learning strategies affect the cultivation of national values.